Prenatal screening of DiGeorge (22q11.2 deletion) syndrome by abnormalities of the great arteries among Thai pregnant women - Kuntharee Traisrisilp; Fuanglada Tongprasert; Kasemsri Srisupundit; Suchaya Luewan; Theera Tongsong (Korean Society of Obstetrics and Gynecology, 2020)
Objective22q11.2DS (deletion syndrome) is one of the common serious anomalies resulting in high perinatal morbidity and mortality rate. Nevertheless, prenatal diagnosis of 22q11.2DS in Southeast Asia has never been described and its prevalence in prenatal series has never been explored. The objective of this study was to describe the experience of prenatal diagnosis of 22q11.2DS in the Thai population and to determine its prevalence among fetuses prenatally diagnosed with abnormalities of the great arteries.MethodsA prospective study was conducted on pregnant Thai women prenatally diagnosed with abnormalities of the great arteries in the second trimester. The recruited cases were investigated for fetal 22q11.2 deletion by in situ hybridization with a probe specific to the DiGeorge/VCFS TUPLE 1 region located on chromosome 22 for the locus D22S75, and 22qter for a telomere specific sequence clone as the control region.ResultsFive out of the 42 (11.9%) fetuses with abnormalities of the great arteries meeting the inclusion criteria were proven to have 22q11.2DS. The most common abnormalities were the tetralogy of Fallot (or variants) and right-sided aortic arch, followed by a thymic hypoplasia.ConclusionAs observed in the western countries, we have documented that, among pregnant Thai women, 22q11.2DS is highly prevalent in fetuses with abnormalities of the great arteries (approximately 12%). This information is important when counselling couples to undergo prenatal testing for 22q11.2DS, since this information is vital in the patients' decision of termination or continuation of pregnancy and in a well-prepared management of the affected child.